Self-reported competence level of occupational health care professionals in work ability risk management and analysis. - Sirkka, Johanna; Suhonen, Riitta; Katajisto, Jouko; Salminen, Leena; Stolt, Minna (Work, 2023)
BACKGROUND: The management and analysis of work ability risks is important to support well-being at work and requires multidimensional competence. Competence evaluation in Occupational Health Care professionals' (OHCP) practice is essential for their professional development and promotion of quality of care. OBJECTIVE: To describe OHCPs' self-reported competence level to manage and analyze work ability risks. METHODS: A descriptive, cross-sectional study design was applied. The data were collected electronically from May to June 2018 using the Comp-WARMA instrument (scale 1 = poor – 4 = excellent) from Occupational Health Care professionals working in Finnish private medical centers (n = 169, response rate of 10%). The data were analyzed statistically. RESULTS: The levels of knowledge and skills of OHCP in work ability risk management and analysis were mainly at good level (3.22 on average), but some deficient were still identified. The knowledge and skills of the work ability risk management and analysis were associated with the number of customer organizations they worked with, their attendance of supplementary training regarding work ability risk management and analysis, their amount of work experience, their type of employment, age, and gender. CONCLUSION: OHCP self-reported competence levels in work ability risk management and analysis was at good level. There is a need for development in all areas of work ability risk management and analysis. OHCP could benefit from in-service education on work ability risk management and analysis. Further validation of the Comp-WARMA instrument in larger sample is needed.